James L. Hansen letter to Thomas Kent regarding birds sighted by himself and others, November 25, 1980 - Hansen, James L.et al (1980)
James L. Hansen letter contains a list of birds sighted including the dates, locations and people involved. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1980. Epson - sheet feed/flatbed